2019
DOI: 10.1016/j.resuscitation.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of cerebral rSO2 monitoring during CPR to predict the probability of return of spontaneous circulation

Abstract: Background: Cerebral oximetry (rSO 2) may be useful in assessing the probability of return of spontaneous circulation (ROSC). However, the potential of assessing the trend in the rSO 2 value has not been discussed when determining the probability of ROSC. Methods: This was a retrospective study of out-of-hospital cardiac arrest (OHCA) patients with continuous rSO 2 values recorded during cardiopulmonary arrest. We used logistic regression analysis at each time point to investigate the best subsets of rSO 2-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 18 publications
3
31
0
Order By: Relevance
“…Furthermore, some authors have suggested that dynamic assessments of rSO 2 obtained throughout resuscitation are more appropriate than static assessments for evaluating outcomes in patients with CA ( 22 ). In a single-center retrospective study, Takegawa et al evaluated the association between the probability of ROSC and the degree of rSO 2 increase during CPR among 90 patients with OHCA, 35 (38.9%) of whom achieved ROSC ( 65 ). Receiver operating characteristic curve (ROC) analysis revealed that the amount of maximum rise in rSO 2 value (i.e., the difference between maximum and baseline values) over a 16-min measurement period yielded an AUC of 0.75 for differentiating between the ROSC and non-ROSC groups.…”
Section: Prediction Of Rosc and Favorable Neurological Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some authors have suggested that dynamic assessments of rSO 2 obtained throughout resuscitation are more appropriate than static assessments for evaluating outcomes in patients with CA ( 22 ). In a single-center retrospective study, Takegawa et al evaluated the association between the probability of ROSC and the degree of rSO 2 increase during CPR among 90 patients with OHCA, 35 (38.9%) of whom achieved ROSC ( 65 ). Receiver operating characteristic curve (ROC) analysis revealed that the amount of maximum rise in rSO 2 value (i.e., the difference between maximum and baseline values) over a 16-min measurement period yielded an AUC of 0.75 for differentiating between the ROSC and non-ROSC groups.…”
Section: Prediction Of Rosc and Favorable Neurological Outcomesmentioning
confidence: 99%
“…Receiver operating characteristic curve (ROC) analysis revealed that the amount of maximum rise in rSO 2 value (i.e., the difference between maximum and baseline values) over a 16-min measurement period yielded an AUC of 0.75 for differentiating between the ROSC and non-ROSC groups. In addition, the best AUC value was achieved by the combination of the amount of maximum rise and baseline rSO 2 , rather than by the amount of maximum rise alone (AUC = 0.91) ( 65 ). The authors suggested that discontinuation of CPR may be indicated in patients with low initial values who do not exhibit an appropriate increase in rSO 2 , resulting in a low mean value.…”
Section: Prediction Of Rosc and Favorable Neurological Outcomesmentioning
confidence: 99%
“…[92][93][94] A trend of rising rSco 2 (between 7% and 15% from baseline measurement) may be a more reliable predictive factor for ROSC. 90,95,96 The ScopRev also identified 2 observational studies of NIRS in children during CPR. One found that cerebral physiological changes were associated with changed NIRS measurements during cardiac arrest, increased intracranial pressure reduction, arrest resolution, and after ROSC.…”
Section: Summary Of Evidencementioning
confidence: 99%
“… 92 , 93 , 94 A trend of rising rS O 2 (between 7% and 15% from baseline measurement) may be a more reliable predictive factor for ROSC. 90 , 95 , 96 …”
Section: Pals: Physiological Monitoring During Arrest To Guide Therapmentioning
confidence: 99%